Model for assessing the financial stability of commercial bank (Journal of Economic Research & Business Administration, 2020)
This article is devoted to a model for assessing the financial stability of a Kazakhstan bank. One ofthe priority tasks for effective management of the bank’s activities is the established work of existingbusiness processes that have a direct impact on financial stability. At the same time, supervisory regulationof the banking sector is aimed at assessing the acceptability of risks taken by second-tier banks and,if necessary, timely adjusting their activities.The hypothesis of the study is the assumption that the Bank’s early diagnosis of the impact of potentialexternal and internal risks on the Bank’s strategic indicators, as well as the effective managementof capital adequacy, serve as the basis for ensuring the financial stability of a commercial bank and itsstable functioning.The study examines the theoretical foundations of solvency, defines the concept of bank stability,studies the factors affecting the financial position of the bank, and defines the main criteria for evaluatingbanks accepted in international practice.This paper gives general recommendations when developing a model for assessing the capital adequacyof a second-tier bank, both when checking the stability of the bank, and in strategic planning tosupport management decisions.